Comparative research on two surface conductivity models for the scattering of electromagnetic wave by the charged sphere. (February 2019) - Gao, Xuan; Wang, Juan; Li, Xingcai
Highlights: We compared two surface conductivity models that can be used in the scattering of electromagnetic wave by the charged spherical particle. The effect of particle size parameter, refractive index, and its charged quantity is analyzed. The different variation laws for the scattered particle and the absorptive particle is discussed. Abstract: The surface conductivity model plays an important role in solving the electromagnetic scattering of microwave by the charged particle. We compared two models that can be used in the scattering of electromagnetic wave by the charged spherical particle. The results show that the extinction efficiency and the scattering efficiency calculated through these two models are much different in some cases, and which also affect by the particle size, refractive index, and its charged quantity. However, when the size parameter of particle is larger enough, the results from these two models became consistent with each other.